THE FINANCIAL TECHNOLOGY, REGULATION AND BANKING ADAPTATION IN INDONESIA - Kennedy, Posma Sariguna Johnson; Harefa, Alvani Amaerita (Universitas Kristen Indonesia, 2018)
This study aims to describe the impact of the application of financial technology to conventional banking institutions in Indonesia in terms of regulators and banks that are adaptation. The data used comes from primary data through direct research into Wisma Mulia Building-Office of Financial Services Authority and through interviews, as well as secondary data through internet media. The methodology used by the authors is with qualitative analysis techniques. The results of the research, sorted by the researchers into three points, namely: innovation disruption, fintech regulation and fintech to banking in Indonesia. The conclusion can be drawn from the research that disruption innovation that occurred in the financial sector with the emergence of fintech is not a phenomenon that must be feared and shunned but is a phenomenon that must be embraced to improve economic growth and prosperity. OJK as an institution that oversees the financial sector strongly supports the presence of fintech by issuing POJK regulation No. 77 / POJK.01 / 2016. For Bank Mandiri and BTPN, fintech can not be considered an ordinary phenomenon but the two banks are taking action to collaborate with fintech actors.Keywords: disruptive innovation, financial sector, conventional banking institutions, financial technology.